Development of Liveworksheets Based E-Worksheets in Pancasila Education Learning for Grade IV Elementary Students in Cluster 1, Talang Muandau District, Bengkalis Regency - Noor, Fadila; Reinita, Reinita; Anita, Yesi; Safitri, Serly (Journal of Educational Sciences, 2025)
This study addresses limited innovation in elementary Pancasila Education, where paper based student worksheets (LKPD) dominate and provide little interactive feedback. It aimed to develop electronic LKPD (E LKPD) on Liveworksheets that are interactive and engaging, thereby improving pupils’ comprehension and involvement. Using the ADDIE Research and Development framework Analysis, Design, Development, Implementation, Evaluation the product was piloted with Grade IV learners: initial trials at SDN 8 Talang Muandau, further research at SDN 20, and full implementation at SDN 11. Content, media, and language experts assessed the E LKPD, awarding an average validity of 90.42 percent, classifying it as “highly valid.” Practicality questionnaires returned scores of 93.66 percent at the trial school, 93.86 percent at the research school, and 95.64 percent at the implementation school, all rated “highly practical.” Effectiveness was tested via pre  and post assessments; Mann–Whitney analysis produced p = 0.000 (< 0.05), confirming significant improvement in learning outcomes after using the E LKPD. The digital format incorporates automatic feedback, multimedia elements, and diversified exercises aligned with the Merdeka Curriculum, making learning more student centred and promoting critical thinking skills. These findings demonstrate that the Liveworksheets based E LKPD is a valid, practical, and effective tool for enriching Pancasila Education in Grade IV.